Cyanobacterial Farming for Environment Friendly Sustainable Agriculture Practices: Innovations and Perspectives - Pathak, Jainendra; Rajneesh,; Maurya, Pankaj K.; Singh, Shailendra P.; Häder, Donat-P.; Sinha, Rajeshwar P. (Frontiers in Environmental Science, 2018)
Sustainable supply of food and energy without posing any threat to environment is the current demand of our society in view of continuous increase in global human population and depletion of natural resources of energy. Cyanobacteria have recently emerged as potential candidates who can fulfil abovementioned needs due to their ability to efficiently harvest solar energy and convert it into biomass by simple utilization of CO2, water and nutrients. During conversion of radiant energy into chemical energy, these biological systems produce oxygen as a by-product. Cyanobacterial biomass can be used for the production of food, energy, biofertilizers, secondary metabolites of nutritional, cosmetics and medicinal importance. Therefore, cyanobacterial farming is proposed as environment friendly sustainable agricultural practice which can produce biomass of very high value. Additionally, cyanobacterial farming helps in decreasing the level of greenhouse gas, i.e., CO2, and it can be also used for removing various contaminants from wastewater and soil. However, utilization of cyanobacteria for resolving the abovementioned problems is subjected to economic viability. In this review, we provide details on different aspects of cyanobacterial system that can help in developing sustainable agricultural practices. We also describe different large-scale cultivation systems for cyanobacterial farming and discuss their merits and demerits in terms of economic profitability.